New insights from old eggs – the shape and thickness of Great Auk Pinguinus impennis eggs. (26th February 2020) - Birkhead, Tim; Russell, Douglas; Garbout, Amin; Attard, Marie; Thompson, Jamie; Jackson, Duncan
Abstract : We compared the shape and eggshell thickness of Great Auk Pinguinus impennis eggs with those of its closest relatives, the Razorbill Alca torda, Common Guillemot Uria aalge and Brünnich's Guillemot Uria lomvia, in order to gain additional insights into the breeding biology of the extinct Great Auk. The egg of the Great Auk was most similar in shape to that of Brünnich's Guillemot. The absolute thickness of the Great Auk eggshell was greater than that of the Common Guillemot and Razorbill egg, which is as expected given its greater size, but the relative shell thickness at the equator and pointed end (compared with the blunt end) was more similar to that of the Common Guillemot. On the basis of these and other results we suggest that Great Auk incubated in an upright posture in open habitat with little or no nest, where its pyriform egg shape provided stability and allowed safe manoeuvrability during incubation. On the basis of a recent phylogeny of the Alcidae, we speculate that a single brood patch, a pyriform egg and upright incubation posture, as in the Great Auk and the two Uria guillemots, is the ancestral state, and that the Razorbill – the Great Auk's closest relative – secondarily evolved two brood patches and an elliptical egg as adaptations for horizontal incubation, which provides flexibility in incubation site selection, allowing breeding in enclosed spaces such as crevices, burrows or under boulders, as well as on open ledges.